Workplace bullying and its impact on the quality of healthcare and patient safety - Al Omar, Munirah (2019)
Background Workplace bullying (WPB) is a physical or emotional harm that may negatively affect healthcare services. The aim of this study was to determine to what extent healthcare practitioners in Saudi Arabia worry about WPB and whether it affects the quality of care and patient safety from their perception. Methods A cross-sectional study was conducted in 2018. An online survey was distributed among all practitioners at a multi-regional healthcare facility. A previously validated tool was sourced from an integrative literature review by Houck and Colbert. Responses to 15 themes were rated on a 5-point Likert scale, converted to percentage mean scores (PMS) and compared across participants’ characteristics using bivariate and regression analyses. Results A total of 1074/1350 (79.5%) completed the questionnaire. The overall median [interquartile range] score of worrying about WPB was 81.7 [35.0]. Participants were mainly worried about the effect of WPB on their stress, work performance, and communication between staff members. A significant negative relationship developed between the quality of care and worrying about WPB, P < 0.001. More educated practitioners were 1.7 times more likely to be worried about WPB compared with their counter group, adj.P = 0.034. Junior practitioners were 1.6 times more likely to be worried about WPB, adj.P = 0.017. The group who has not been trained in handling WPB (1.7 times), and those who had been exposed to WPB (2.2 times) were both more likely to be worried about WPB compared with their counter groups, adj.P = 0.026 and adj.P < 0.001 respectively. Conclusions Most healthcare practitioners worry about WPB, especially its negative impact on the quality of care and patient safety. A greater proportion of practitioners with higher levels of education and their less experienced counterparts were more worried about WPB. Previous exposure to a WPB incident amplifies the practitioners’ worry, but being trained on how to counteract bullying incidents makes them less likely to be worried.